2017
DOI: 10.24200/sci.2017.4397
|View full text |Cite
|
Sign up to set email alerts
|

An integrated train scheduling and infrastructure development model in railway networks

Abstract: Abstract. The evaluation of the railway infrastructure capacity is an important task of railway companies. The goal is to nd the best infrastructure development plan for scheduling new train services. The question addressed by the present study is how the existing railway infrastructure can be upgraded to decrease the total delay of existing and new trains with minimum cost. To answer this question, a mixed-integer programming formulation is extended for the integrated train scheduling and infrastructure devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Other methods involve using the ε-constraint method and applying multi-objective optimization with distance-based methods [27]. Several mixed-integer programming models have been proposed to solve the scheduling problem for single-track railways [28], to integrate train-stop planning and timetabling in high-speed railways [29], to solve the timetable and train-set circulation plans in transition times for high-speed lines [30], to solve the problem of multiperiodic train timetabling and routing high-speed trains at stations [31], to integrate the line planning, timetable and rolling stock allocation problem [32], to integrate the timetable problem with passengers' train booking decisions [33], and to solve the schedules of trains on a railway network to determine the best stop locations for both technical and religious services [34]. Passenger waiting time has also been included in optimization [35] by treating passenger behaviour as deterministic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other methods involve using the ε-constraint method and applying multi-objective optimization with distance-based methods [27]. Several mixed-integer programming models have been proposed to solve the scheduling problem for single-track railways [28], to integrate train-stop planning and timetabling in high-speed railways [29], to solve the timetable and train-set circulation plans in transition times for high-speed lines [30], to solve the problem of multiperiodic train timetabling and routing high-speed trains at stations [31], to integrate the line planning, timetable and rolling stock allocation problem [32], to integrate the timetable problem with passengers' train booking decisions [33], and to solve the schedules of trains on a railway network to determine the best stop locations for both technical and religious services [34]. Passenger waiting time has also been included in optimization [35] by treating passenger behaviour as deterministic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors proposed to address the sudden change in the aerodynamic load of the train by increasing the wind-break wall or optimizing the train structure [16]. Shakibayifar M. found that the failure to implement relevant wind prevention and sand fixation measures in the bridge-road embankment transition sections of wind-sand areas can seriously affect the operation efficiency of high-speed trains and reduce the economy of railroad transportation [17].…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, most railway signalling functions require knowledge of the occupancy status of portions of track called "zones". This parameter is necessary for the efficient and safe planning of trains [1]. In a zone, the traffic and presence of trains is detected by means of a "track circuit".…”
Section: Introductionmentioning
confidence: 99%